Osteoblastic and chondroblastic response to a variety of locally administered immunomodulators in mice - Włodarski, K H; Galus, K (Folia biologica, 1992)
Administration into mouse shank muscles of various immunomodulators which directly or indirectly activate lymphocytes (BCG, Con A, Carrageenan IV, Dextran, PHA-M, PWM, lipopolysaccharides from Corynebacterium) have a dual effect on local bones, stimulating both periosteal bone formation and bone resorption, the former being dominant. These effects vary in frequency and magnitude, the most potent stimulation of periosteal bone formation being observed after administration of Con A and BCG in complete Freund adjuvant. BCG was also a strong inducer of bone resorption in vivo. Concanavalin A and, to a lesser degree, other immunomodulators applied, when administered subcutaneously into the pinna, also have induced perichondrial chondrogenesis. These novel effects of immunodulators could be applied in the field of skeletal tissues regeneration.
Keywords: Osteoblasts; Bone and Bones; mužské pohlaví; Mice; Mice, Inbred Strains; inbrední kmeny myší; Cartilage; Osteogenesis; resorpce kosti; Bone Resorption; kosti a kostní tkáň; osteoblasty; osteogeneze; ženské pohlaví; zvířata; chrupavka; myši; adjuvancia imunologická; Adjuvants, Immunologic; Female; Male; Animals